2001
DOI: 10.1002/micr.1057
|View full text |Cite
|
Sign up to set email alerts
|

Silicone rubber tubulization in peripheral sensory nerve reconstruction: An experimental study in rabbits

Abstract: Silicone rubber (polydimethyl siloxane) tubes are used clinically in peripheral nerve reconstruction. A disadvantage of this procedure is that the material often has to be removed owing to its mechanical properties. The aim of our study was to investigate the healing of reconstructed sensory nerves tubulized by silicone rubber in an animal model. In our experiments, we reconstructed the saphenous nerves in 27 rabbits. In series 1 (n = 12), silicone rubber tubes were slid over a nerve suture without a gap. In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…[30][31][32][33][34] Similarly, it has already been determined that an entubulated end-to-end coaptation has no effect on nerve regeneration. 35 Continuous release of nanogram quantities of GDNF on the distal suture of autologous nerve grafts over a period of 6 weeks gave opposite results in the two groups of the study, i.e., immediate or 7-month delayed repair. In the immediate repair group, no, and even a tendency of worse results, were obtained with GDNF.…”
Section: Discussionmentioning
confidence: 93%
“…[30][31][32][33][34] Similarly, it has already been determined that an entubulated end-to-end coaptation has no effect on nerve regeneration. 35 Continuous release of nanogram quantities of GDNF on the distal suture of autologous nerve grafts over a period of 6 weeks gave opposite results in the two groups of the study, i.e., immediate or 7-month delayed repair. In the immediate repair group, no, and even a tendency of worse results, were obtained with GDNF.…”
Section: Discussionmentioning
confidence: 93%
“…This provided the motivation for studying the tissue–biomaterial response of melanin with the sciatic nerve. Silicone was chosen as a control material since it generates a mild, short-term immune response [16] and has been used as a biomaterial for peripheral nerve reconstruction in previous studies [17]. Melanin samples were prepared by drop casting 100 μL of 8% (w/v) melanin in DMSO solution onto smooth PDMS substrates.…”
Section: Methodsmentioning
confidence: 99%
“…80,81 Lundborg et al 82 showed this operational distance could be extended to 15 mm in rat sciatic nerve if synthetic filaments were inserted into the tubes. Eight polyamide filaments with a diameter of 250 m, placed inside silicone tubes with an inner diameter of 1.8 mm, helped sensory fibers bridge the gap and extend into the distal nerve segment, supported by a positive pinch reflex and positive staining for neurofilaments in the distal segment.…”
Section: Synthetic Longitudinal Matricesmentioning
confidence: 97%